Examination of Estate Marketing Practices in Ikeja, Lagos, Nigeria (International Journal of Built Environment and Sustainability, 2017)
Estate marketing is an aspect of the profession of Estate Surveying and Valuation in Nigeria. Previous studies on estate marketing identified that there are challenges affecting estate marketing and the resultant effect on these challenges affects the credibility of the profession of Estate Surveying and Valuation in Nigeria. This necessitates the need to examine the practice of estate marketing in Nigeria. This study examined estate marketing practice among estate surveyors and valuers in Ikeja, Lagos Nigeria. The sample size for the study is the 64 registered Estate Surveying and Valuation firms in the study area. Data gathered were analyzed using descriptive statistics and 5-point likert ordinal scale. Findings from the study revealed that the use of brochure or bulletin is the most common estate marketing method in the study area. Also, it was revealed from the study that the use of press is the most cost effective method of estate marketing in the study area. The study identified the various challenges of estate marketing. However, collection of double professional fees is the most prevalent challenge of estate marketing in the study area. Finally, aggressive marketing which leads to unethical practices is the most prevalent mitigating measures adopted by Estate Surveyors and Valuers in the study area. Recommendations were made on how to review the ethical regulations guiding the practice of Estate Surveying and Valuation which will consequently improve marketing in the study area.